Single dose oral acemetacin for acute postoperative pain in adults. - Moore, R; Derry, S; McQuay, H (2009)
BACKGROUND: Acemetacin is a non-steroidal anti-inflammatory drug (NSAID) licensed for use in rheumatic disease and other musculoskeletal disorders in the UK, and widely available in other countries worldwide. This review sought to evaluate the efficacy and safety of oral acemetacin in acute postoperative pain, using clinical studies of patients with established pain, and with outcomes measured primarily over 6 hours using standard methods. This type of study has been used for many decades to establish that drugs have analgesic properties. OBJECTIVES: To assess the efficacy of single dose oral acemetacin in acute postoperative pain, and any associated adverse events. SEARCH STRATEGY: We searched CENTRAL (Issue 2, 2009), MEDLINE via Ovid (1966 to May 2009); EMBASE via Ovid (1980 to May 2009); the Oxford Pain Relief Database (1950 to 1994); and reference lists of articles. SELECTION CRITERIA: Randomised, double-blind, placebo-controlled clinical trials of oral acemetacin for relief of acute postoperative pain in adults. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed trial quality and extracted data. The area under the "pain relief versus time" curve was used to derive the proportion of participants with acemetacin and placebo experiencing least 50% pain relief over 4 to 6 hours, using validated equations. The number needed to treat to benefit (NNT) was calculated using 95% confidence intervals. The proportion of participants using rescue analgesia over a specified time period, and time to use of rescue analgesia, were sought as additional measures of efficacy. Information on adverse events and withdrawals was also collected. MAIN RESULTS: No study fulfilled the inclusion criteria. AUTHORS' CONCLUSIONS: In the absence of randomised evidence of efficacy for oral acemetacin in acute postoperative pain, we cannot, at present, make any conclusions regarding its effectiveness. Because trials clearly demonstrating analgesic efficacy in the most basic of acute pain studies is lacking, use in other indications should be evaluated carefully. Given the large number of available drugs of this kind and similar classes, there is no urgent research agenda for this drug.